Expression of ZENK and FOXP1 gene in a brain of a parrot - Yazid, Nurul Afiqah (2015)
Parrots are one of the songbirds that are well known for their vocalization skills. Based on previous study, the production of songbirds is being controlled by the forebrain and also related with changes of some genes expression that is responsible for song perception and production. Although many studies on the genes expression associated with the learning and memory development in humans are being reported, limited findings are reported on genes related with the songbird. The ZENK and FOXP1 are the most likely genes that are responsible in the songbird. Therefore, we conducted a study to analyze the gene expression associated with songbirds which are ZENK and FOXP1. A brain tissue of dead parrot was obtained and preserved in RNAlater. The RNA extraction was done followed by qPCR for quantification of the FOXP1 and ZENK expression in the sample. Gel electrophoresis was done and result shows that there is presence of FOXP1 and ZENK in the parrot brain. Different RNA concentration was used which are 170 ng/ml, 17 ng/ml, 1.7 ng/ml, 0.17 ng/ml and 0.02 ng/ml respectively. The result was documented as cycle threshold (CT) value. In RNA concentration of 170 ng/ml, the lowest CT value was recorded which are 22.91 in ZENK and 23.39 in FoxP1 while RNA concentration of 0.02 ng/ml has CT value of 23.94 for ZENK and 23.99 for FOXP1. As the CT value is indirectly proportional to gene expression, we are able to conclude that genes are presence in high amount in a high concentration of RNA.